TREATING CERVICAL CANCER WITH HERBS: A REVIEW - Joseph, Anitha; Dhanraj, Kiruthika; Ramalingam, Sivakumar; Saravanan, Renuka (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Medicinal plants have been on the forefront where research on the anticancer agent is planned. This review mainly focuses on several such as medicinal plants Rosmarinus officinalis, Solanum nigrum, Kaffir lime, and Garcinia nujiangensis used in the treatment of cervical cancer and the secondary metabolites derived from different plant sources. Plant molecules such as cisplatin, curcumin (-)- epigallocatechin (EGC)-3-gallate, EGC, epicatechin- 3-gallate, and other catechins that have a wide range of biological properties and the molecular mechanism with different cells were reviewed. This review will promote the research on the development of a plant-derived anticancer drug with lesser or no side effects and aid in understanding the mechanism of action of several plant-derived molecules.